Iranian nurses' views on barriers to moral courage in practice: A qualitative descriptive study - Mahnaz Rakhshan; Noushin Mousazadeh; Hamideh Hakimi; Fahimeh Alsadat Hosseini (BMC, 2021)
Abstract Background Nursing is a caring profession. Due to the nature of their work, nurses need to have the moral courage to deliver safe nursing care. Research results have reported a low level of moral courage in the majority of nurses. The current study aimed to identify the barriers to show moral courage in Iranian nurses. Methods This study was qualitative research that was conducted using conventional content analysis. Data was gathered using in-person, semi-structured, in-depth interviews. Interviews were conducted from March to September 2020. Purposeful sampling was used and sampling was continued until data saturation was reached. Participants were 19 nurses working in hospitals in Iran. Results According to data analysis, six categories and three themes were extracted. Themes are "organizational failure", "deterrent personal identity" and "defeated professional identity". Conclusions The results of this study revealed the barriers to show moral courage which were usually overlooked in previous quantitative studies. It appears that the elimination of these barriers is an effective step in the improvemalet of nurses' competencies. The results of this study can be helpful in the developmalet of programs to address the factors affecting nurses' moral courage.